The Effects of Conventional, Warm and Cold Acupressure on the Pain Perceptions and Beta-Endorphin Plasma Levels of Primiparous Women in Labor: A Randomized Controlled Trial - Altinayak, Serap Ozturk; Ozkan, Hava (Elsevier Science Inc, 2022)
Objective: This study was performed to determine the impact of different acupressure procedures, performed on women's hands during labor, on beta-endorphin plasma levels and labor pain perception. Design: Randomized controlled experimental trial Setting and Participants: This study was conducted with 140 pregnant women in the delivery rooms of a university research and training hospital and a state hospital in a province in the Black Sea Region of Turkey. Methods: This study was conducted with three experimental groups (who had conventional, warm and cold acupressure on their LI4 acupressure point) and one control group (no acupressure). Each group included 35 pregnant women. The data were collected using a personal information form, the Labor Intervention Followup Form, the Visual Analog Scale (VAS) and the Verbal Category Scale (VCS). Its main outcomes were the women's labor pain perceptions and beta-endorphin plasma levels. Results: The experimental and control groups had homogeneous introductory characteristics. The experimental groups had significantly higher mean VAS and VCS posttest scores than the control group (p<0.001). The experimental groups' mean posttest beta-endorphin plasma levels were also significantly higher (p <0.05). Conclusion: In this study, conventional, warm and cold acupressure reduced the women's labor pain and increased their beta-endorphin plasma levels. Midwives can use acupressure to reduce labor pain. (C) 2022 Elsevier Inc. All rights reserved.
Öztürk Altınayak, Serap/0000-0002-3882-0966;
Keywords: Acupressure; Labor Pain; Midwifery; Pregnant Woman; Beta-Endorphin